الفتوى المباشرة عن التباعد بين المصلّين في صلاة الجماعة في الواقع الماليزي ومدى انضباطها بالضابط حسن اختيار وسيلة التعبير عن الفتاوى: دار الإفتاء بولاية قدح نموذجا = The direct fatwa on the spacing of congregants in the congregational prayer in the Malaysian reality and the extent of the extent of it’s compliance to regulation "good choice of means of expressing fatwas”: Mufti Office of Kedah as a example. - Ab Razak, Mohamed Rashid; Ismail, Abdul Manan (2021)
يتناول هذا البحث الفتوى المباشرة عن قضية التباعد بين المصلين في صلاة الجماعة ومدى انضباطها بضابط حسن اختيار وسيلة التعبير عن الفتاوى من قبل المفتي وتركّز الدراسة على الفتوى المباشرة التي أصدرها دار الإفتاء بولاية قدح. ويتم البحث من خلال استخدام المنهج الوصفي التحليلي لوصف ماهية الموضوع وتتبع آراء الفقهاء في شأنها ودارستها في المراجع المعتبرة في الفقه الإسلامي ثم الخروج بنتيجة معقولة مناسبة. ويأتي الباحث بالتوجيهات والقيم من الأحكام الإسلامية وربطها بالواقع الحالي الماليزي كما يقوم الباحث بتحليل الفتوى المباشرة من دار الإفتاء بولاية قدح في هذا الشأن وقد استنتج الباحث أن هذه الفتوى المباشرة منضبطة بهذا الضابط ************************************************************************************ This research deals with the direct fatwa on the issue of spacing between worshipers in the congregational prayer and the extent of it’s complience to regulation with a good control over the means of expressing fatwas by the mufti. The research is done through the use of the descriptive and analytical method to describe the essence of the topic and follow the opinions of the jurists regarding it and study it in the recognized references in Islamic jurisprudence, then come up with a reasonable and appropriate result. The researcher comes with directives and values from Islamic rulings and links them to the current Malaysian reality. The researcher also analyzes the direct fatwa from the Fatwa House in the state of Qadah in this regard, and the researcher concluded that this direct fatwa is complied with this regulation.